Bidirectional catalyst with robust lithiophilicity and sulfiphilicity for advanced lithium–sulfur battery - Li, Yanan (2023)
The application of lithium–sulfur batteries (LSBs) is immensely impeded by notorious shuttle effect, sluggish redox kinetics, and irregular Li2S deposition, which result in large polarization and rapid capacity decay. To obtain the LSBs with high energy density and fast reaction kinetics, herein, a heterostructure composed by nitrogen-deficient graphitic carbon nitride (ND-g-C3N4) and MgNCN is fabricated via a magnesiothermic denitriding technology. Lithophilic C3N4 with abundant nitrogen-deficient acts as a conductive framework, together with the sulfiphilic MgNCN, lithium-polysulfides (LiPSs) can be effectively captured followed by a regulated Li2S nucleation. Furthermore, the oxidation conversion kinetics can be accelerated as well. As expected, the LSBs with catalytic MgNCN/ND-g-C3N4 as the interlayer exhibit remarkable electrochemical performance with a discharge capacity of 650 mAh g−1 at 4 C. Meanwhile, a low capacity decay of 0.008% per cycle can be reached at 1 C after 400 cycles. Even with a high areal sulfur loading of 5.1 mg cm−2, outstanding capacity retention can be achieved at 0.5 C (64.18%) and 1 C (90.46%). The presented strategy unlocks a new way for the LSBs design with highly efficient catalyst.